Prognostic Implication of Longitudinal Changes of Left Ventricular Global Strain After Chemotherapy in Cardiac Light Chain Amyloidosis - Bak, Minjung; Kim, Darae; Choi, Jin-Oh; Kim, Kihyun; Kim, Seok Jin; Jeon, Eun-Seok (Frontiers in Cardiovascular Medicine, 2022)
Aims Cardiac involvement is the main prognostic determinant in AL amyloidosis. We sought to determine the prognostic significance of longitudinal change of left ventricular (LV) global longitudinal strain (GLS) in cardiac light chain (AL) amyloidosis patients undergoing chemotherapy. Method and Result We retrospectively investigated 117 cardiac AL amyloidosis patients who underwent chemotherapy from 2005 to 2019. All patients underwent comprehensive 2D conventional transthoracic echocardiography at baseline and after completion of first-line chemotherapy. Speckle tracking analysis of images was performed offline. Absolute value of LV GLS was expressed as [LV GLS] and change of [LV GLS] after chemotherapy was expressed as ∆ [LV GLS]. Clinical outcomes including cardiac response and all-cause mortality were analyzed. Baseline clinical and echocardiographic parameters were similar in patients with and without CR. ∆ [LV GLS] significantly differed between the CR and non-CR groups (0.4 ± 2.8% in the CR group vs. -0.6 ± 2.5% in the non-CR group, P value=0.046). ∆ [LV GLS] showed satisfactory predictive performance for all-cause mortality (cut-off value=0.8%, AUC 0.643, 95% CI [0.537 – 0.748]). Adding Δ [LV GLS] to the Mayo stage + pre-chemotherapy [LV GLS] model showed incremental prognostic value (C-index: 0.637 vs. 0.708; Relative Integrated Discrimination Index 0.07, P value= 0.003; Net Reclassification Improvement 0.54, P value <0.001). ∆ [LV GLS] showed good correlation with cardiac response (AUC 0.820, 95% CI [0.737-0.904]). Conclusion In cardiac amyloidosis patients who underwent chemotherapy, longitudinal change of [LV GLS] after chemotherapy showed significant association with overall survival as well as cardiac response.